PERTANIAN BERKELANJUTAN: SEBUAH UPAYA UNTUK MEMADUKAN PENGETAHUAN FORMAL DAN INFORMAL PETANI (Kasus pada Petani Hortikultura di Provinsi Jawa Barat) - Gema Wibawa Mukti; Rani Andriani Budi Kusumo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
This study aims to explain why informal knowledge is important for sustainable agricultural development, and finally we try to provide input to increase informal knowledge from farmers in agribusiness centers in West Java Province. The selected informants are farmers who are engaged in horticultural business, have connections and contributions to agricultural development in rural areas and have a role in developing knowledge. Information is collected through various methods that involve in-depth interviews as well as in-depth observations. Farmers' informal knowledge has contributed a lot to the development of sustainable and resilient agriculture. Formal institutions need to pay attention to social, ecological and local economic aspects, focusing on farmers' needs, and not on knowledge that is readily generalized to farmers. Agriculture in a dynamic, complex and local specific context demands a more inclusive, participatory, collaborative model and stronger integration between actors. All actors in the field of horticultural agriculture, especially farmers, must be recognized as equal parties both formally and informally. Collaboration of all parties needs to be improved and integrated in the process of developing horticultural agriculture so that it becomes a stronger and more sustainable business.